Poland’s Population Ageing by Regions, in 1995-2035 Years - Wolańska, Wioletta (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The second transition manifesting in the preference of informal relationships, decreased death rate, longer life, increased migration, strive for maximum use of education, income, and increased life standard and quality contribute to the decreased birth rate (below the level ensuring linear replacement of generations) lids to ageing of population. It is a process in which changes occur in population age structure and an increase in the number and proportion of older people (especially people aged over 65) in the general population, as well as a decrease in the number of young people. This process leads to outcomes which, apart from demographic implications, are of socioeconomic significance and influence changes in the structure of consumption, income and savings distribution, decrease in labour productivity, changes in household structure, healthcare and social care for the elderly. This is why questions resulting from ageing of the population must be an element of adequate social policy. The aim of the paper is an evaluation of Poland's population ageing by regions, in 1995-2035 years.